2019
DOI: 10.1007/s40265-019-01074-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of Post-transplant Hyperparathyroidism and Bone Disease

Abstract: Significant advances in immunosuppressive therapies have been made in renal transplantation, leading to increased allograft and patient survival. Despite improvement in overall patient survival, patients continue to require management of persistent post-transplant hyperparathyroidism. Medications that treat persistent hyperparathyroidism include vitamin D, vitamin D analogues, and calcimimetics. Medication side effects such as hypocalcemia or hypercalcemia, and adynamic bone disease, may lead to a decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 96 publications
1
16
0
3
Order By: Relevance
“…Importantly in the present context, late post-transplantation anaemia 14 and persistent secondary hyperparathyroidism 15 have been reported in up to 35% and 50% of kidney transplant recipients, respectively. Conceptually, anaemia and hyperparathyroidism could mediate impaired diastolic function in kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 60%
“…Importantly in the present context, late post-transplantation anaemia 14 and persistent secondary hyperparathyroidism 15 have been reported in up to 35% and 50% of kidney transplant recipients, respectively. Conceptually, anaemia and hyperparathyroidism could mediate impaired diastolic function in kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 60%
“…PT-HPT occurs in 45 and 20% of kidney transplantation recipients after 2 years and 5 years, respectively [1]. The main cause of PT-HPT is enlarged and autonomous adenomas with dysregulated metabolic bone mineral parameters, even when the renal function of the allograft recovers to normal [3]. Studies have reported that PT-HPT is associated with an elevated risk of fractures, cardiovascular disease, allograft loss (5%) and mortality (4%) [4, 5, 11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Following kidney transplantation, parathyroid hyperplasia may slowly regress during recovery [2]. However, persistent post-transplant hyperparathyroidism (PT-HPT) is common because monoclonal parathyroid tissue either has a reduced response or lacks the typical response to physiologic regulatory mechanisms of parathyroid secretion and proliferation [3]. PT-HPT puts patients at high risk for bone fractures, mortality and renal graft loss [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that subtotal parathyroidectomies may have an increased risk of recurrent HPT (from 5% to 30%) compared to total parathyroidectomies, the subtotal parathyroidectomies are associated with lower rates of hypoparathyroidism and preservation of renal function 14,16,17 . There is evidence that removal of parathyroid tissue accompanied by an abrupt decrease in PTH is related to worsening renal function, possibly due to the loss of the vasodilatory effect of PTH in afferent renal arteriole and vasoconstrictor effect in efferent renal arteriole 15,18 .…”
Section: Discussionmentioning
confidence: 99%